b. \(\frac{x^3}{8}=\frac{y^3}{64}=\frac{z^3}{216}\Rightarrow\left(\frac{x}{2}\right)^3=\left(\frac{y}{4}\right)^3=\left(\frac{z}{6}\right)^3\Rightarrow\frac{x}{2}=\frac{y}{4}=\frac{z}{6}\)
\(\Rightarrow\frac{x^2}{4}=\frac{y^2}{16}=\frac{z^2}{36}\)
Theo t/c dảy tỉ số = nhau:
\(\frac{x^2}{4}=\frac{y^2}{16}=\frac{z^2}{36}=\frac{x^2+y^2+z^2}{4+16+36}=\frac{14}{56}=\frac{1}{4}\)
=> \(\frac{x^2}{4}=\frac{1}{4}\Rightarrow x^2=\frac{1}{4}.4=1=1^2=\left(-1\right)^2\Rightarrow x=\)+1
=> \(\frac{y^2}{16}=\frac{1}{4}\Rightarrow y^2=\frac{1}{4}.16=4=2^2=\left(-2\right)^2\Rightarrow y=\)+2
=> \(\frac{z^2}{36}=\frac{1}{4}\Rightarrow z^2=\frac{1}{4}.36=9=3^2=\left(-3\right)^2\Rightarrow z=\)+3
Vậy có 2 cặp (x;y;z) là: (1;2;3) và (-1;-2;-3).
a. Áp dụng t/c tỉ số = nhau làm tương tự.